Inovação, universidade e desenvolvimento regional: um estudo sobre as patentes desenvolvidas pela UFT - Oliveira, Pedro Eliagi de (Universidade Federal do Tocantins, 2020)
Brazilian universities are incorporating in their mission to contribute to regional development through teaching, research and extension, which are the pillars responsible for the transfer of knowledge produced within the institution. Located in the northern region of Brazil, in the state of Tocantins, the Federal University of Tocantins (UFT), object of study of this research, has a structure with established human and physical capital, which is able to contribute to the development of the state by through innovation. The general objective of this research is to study the innovation system of the Federal University of Tocantins (UFT) and to relate it to the productive chains of Tocantins. The methodology used in the research was quantitative and documentary, using secondary data from the NIT (UFT), the research report of the Entrepreneurial Universities Ranking and the Federation of Industries of Tocantins (FIETO). The results show an exponential growth in patent registrations since the start of NIT (UFT) activities in 2012, with patents distributed in 5 of the 7 major areas of knowledge recognized by CAPES and international standards. In the production chains, patents were registered in 11 different chains, with various applications in agriculture, transportation, construction, food, chemical industry and collection or treatment of urban waste.